Scheduling for Multi-Cell Caching: Hit Maximization Subject to Age of Information - Deng, Tao; Yu, Zhanwei; Yuan, Di (IEEE transactions on vehicular technology, 2023)
In this paper, we investigate how to schedule content updates for multi-cell caching networks. We model a hit ratio maximization problem subject to age of information (AoI), and prove the NP-hardness of the problem. For problem solving, we propose a scalable and effective algorithm based on repeated cutting plane (RCP), in which a cutting plane algorithm and a rounding algorithm are implemented iteratively. In addition, we derive a bound that serves as a benchmark of any suboptimal solution. Performance evaluations show that for RCP, the performance gap to optimum is less than 2.5%.